Medical vocation in physicians with prestigious professional behavior - Perales, Alberto (2013)
Purpose: To study medical vocation from a scientific perspective. Objectives: To analyze origins and development-associated factors ofmedical vocation in physicians considered examples of high-level professional behavior and medical vocation. Design: Qualitative study, withtypical case sampling and in-depth interviews. Setting: Institute on Ethics in Health, Faculty of Medicine, Universidad Nacional Mayorde San Marcos, Lima, Peru. Participants: Physicians. Methodology: The sample consisted in 76 physicians selected by pre-establishedcriteria from the four more prestigious Peruvian medical institutions: National Academy of Medicine, Peruvian Academy of Surgery,San Marcos University’s and Peruvian Cayetano Heredia University’s Schools of Medicine. Informed consent was previously obtained.Main outcome measures: Medical vocation origins and associated factors. Results: Eighty-two per cent of physicians interviewed weremale, 71.6 year-old average with range 49-88 years; only in 8% their father was MD also and in 14% a family member was MD. In 30%the physician was the oldest son/daughter. Medical vocation did not follow a unique pattern and begun in different periods of the vitalcycle even after the student had been admitted to the School of Medicine. Most frequently associated factors were personal dynamicsand family influence, and in two cases no explanation was found. Upon results vocation and medical vocation definitions are proposed.Conclusions: Data analysis allows understanding medical vocation as a process generated in a human being on account of two factors:individual (the subject) and social (the environment that stimulates its development). Its beginning may occur at different ages and inseveral ways, finally becoming part of the ‘oneself project’ (specific examples are given).